Safety and immunogenicity of the novel seasonal preservative‐ and adjuvant‐free influenza vaccine: Blind, randomized, and placebo‐controlled trial. Issue 1 (25th September 2017) - Sarsenbayeva, Gulbanu; Volgin, Yevgeniy; Kassenov, Markhabat; Issagulov, Timur; Bogdanov, Nikolay; Sansyzbay, Abylay; Abitay, Ruslan; Nurpeisova, Ainur; Sagymbay, Altynay; Koshemetov, Zhumagali; Stukova, Marina; Buzitskaya, Zhanna; et al.
Abstract : The producers of influenza vaccines are not capable today to meet the global demand for an influenza vaccine in case of pandemic, so the World Health Organization recommends to develop the own influenza vaccine production in each country. A domestic preservative‐ and adjuvant‐free trivalent split vaccine against seasonal influenza was developed at the Research Institute for Biological Safety Problems. The paper presents the results of assessing safety and immunogenicity of the influenza split vaccine after single immunization of healthy volunteers aged 18‐50 years in the course of Phase I Clinical Trials. This study was randomized, blind, and placebo‐controlled. The volunteers were intramuscularly vaccinated with a dose of split vaccine or placebo. The study has shown that all local and systemic reactions had low degree of manifestation and short‐term character, so there was no need in medication. Serious side effects were not observed. On day 21 post vaccination the portion of vaccinated persons with fourfold seroconversions to influenza А/H1N1pdm09 virus was 100.0%, to influenza А/H3N2 virus—95.5%, to influenza B virus—81.8%, and in placebo group this index was 0%. Seroprotection rates against influenza А/H1N1pdm09, А/H3N2 and B viruses were 95.5, 86.3, and 72.7%, respectively. Geometric mean titers (GMT) of antibodies by day 21 post vaccination reached 175.7 for influenza А/H1N1pdm09 virus, 64.2 for influenza А/H3N2 virus, and 37.6 for influenza B virus; in placebo group GMT growth was not observed. So, the seasonal influenza split vaccine is well tolerated and fits all immunogenicity criteria for human influenza vaccines.